Regulatory and Ethical Duality in Indonesia's Fintech P2P Lending: Conventional vs. Sharia Models from an Islamic Economics Perspective - Latifah, Leti (Al-Muhasib: Journal of Islamic Accounting and Finance, 2025)
Abstract: This study employs an Islamic economics perspective to comparatively analyze both systems' operational frameworks, compliance challenges, and socio-economic impacts. The rapid expansion of fintech peer-to-peer (P2P) lending in Indonesia reveals a regulatory and ethical duality between conventional and Sharia models. Through qualitative document analysis of OJK regulations, DSN-MUI fatwas, and fintech platforms (2019-2024), we identify how conventional P2P lending relies on interest-based mechanisms that contradict Islamic principles of riba prohibition, while Sharia P2P financing utilizes murabahah, mudharabah, and musyarakah contracts to ensure ethical transactions. Key findings demonstrate: (1) Tension between OJK's unified fintech supervision and DSN-MUI's Sharia governance requirements, (2) 38% higher financial inclusion for MSMEs under Sharia models despite lower market penetration, and (3) Critical literacy gaps enabling illegal lending platforms. We argue that reconciling this duality requires regulatory harmonization, integrating POJK's risk frameworks with maqashid al-shariah objectives. This research contributes a policy blueprint for Muslim-majority economies navigating digital finance ethicalization.Abstrak: Studi ini mengkaji dualitas regulasi dan etika dalam fintech P2P lending Indonesia melalui perspektif ekonomi Islam, membandingkan secara analitis model konvensional berbasis bunga dengan skema Syariah berbasis akad murabahah, mudharabah, dan musyarakah. Berbasis analisis dokumen kualitatif terhadap regulasi OJK (POJK No. 10/2022), fatwa DSN-MUI (No. 117/2018), dan operasional platform fintech periode 2019-2024, temuan mengungkap tiga dinamika kritis: (1) Ketegangan struktural antara kerangka pengawasan terpadu OJK dan persyaratan syariah DSN-MUI, (2) Capaian inklusi keuangan UMKM 38% lebih tinggi pada model Syariah meski penetrasi pasarnya lebih rendah, dan (3) Kerentanan sistemik akibat literasi digital yang minim yang dimanfaatkan platform ilegal. Penelitian menyimpulkan bahwa rekonsiliasi dualitas memerlukan harmonisasi kebijakan yang mengintegrasikan manajemen risiko POJK dengan prinsip maqashid al-shariah (pelestarian agama, jiwa, akal, keturunan, dan harta), sekaligus menawarkan blueprint regulasi bagi negara mayoritas Muslim dalam membangun ekosistem keuangan digital yang etis dan berkelanjutan.